1999
DOI: 10.1093/jat/23.4.280
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Fentanyl and Related Compounds IV. Chromatographic and Spectrometric Discrimination of Fentanyl and its Derivatives

Abstract: Chromatographic and spectrometric discrimination of fentanyl and its 24 analogues are discussed. Twenty-three of 25 samples were discriminated from each other by gas chromatography (GC), and the combination of GC and mass spectrometry enabled discrimination of all 25 samples. Condensed-phase infrared spectrometry was also useful for the differentiation of structurally similar compounds, but vapor-phase infrared spectra were not useful for discrimination of fentanyls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 4 publications
2
50
0
Order By: Relevance
“…Based on the GC‐MS data alone, we arrived at the hypothesis, that the unknown compound was the acryloyl derivative of fentanyl (acrylfentanyl). Following the EI fragmentation patterns for fentanyl and related compounds published by Ohta et al .,32 the bond cleavage points can be assigned (Figure 3). Three fragment ions for acrylfentanyl (Figure 3B) differ with 2 Da from those of fentanyl (Figure 3A): m / z 243 (base peak), m / z 200 (from the piperidine ring), and m / z 55 (from the acryloyl group).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the GC‐MS data alone, we arrived at the hypothesis, that the unknown compound was the acryloyl derivative of fentanyl (acrylfentanyl). Following the EI fragmentation patterns for fentanyl and related compounds published by Ohta et al .,32 the bond cleavage points can be assigned (Figure 3). Three fragment ions for acrylfentanyl (Figure 3B) differ with 2 Da from those of fentanyl (Figure 3A): m / z 243 (base peak), m / z 200 (from the piperidine ring), and m / z 55 (from the acryloyl group).…”
Section: Resultsmentioning
confidence: 99%
“…Fentanyl analogues with a methyl group (e.g., α-methyl, 3-methyl, p-methyl, n-butyryl, and isobutyryl) were synthesized in accordance with previous reports [6,7,[10][11][12][13][14][15].…”
Section: Synthesis Of Fentanyl Analoguesmentioning
confidence: 98%
“…These compounds had high potential for abuse, because of their ease of synthesis and high analgesic activity. The structures of fentanyl (1) and 11 synthesized analogues (2-12) examined in this study are shown in Tables 1-4. Although there are a number of reports regarding the analgesic activities of some of these analogues [8][9][10][11][12][13][14][15], there have been only a few reports on the actually abused analogues [8]; there have been no reports on α-methylfentanyl (2), the most widely abused analogue. Furthermore, comparison of their analgesic activities with those of morphine and fentanyl was not described.…”
Section: Introductionmentioning
confidence: 99%
“…7) Furthermore, several discrimination methods for fentanyl and its analogues have been reported. [8][9][10][11][12][13] The structures of fentanyl, 3-methylfentanyl and α-methylfentanyl are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%